Does Ribosomal DNA Get Out of the Micronuclear Chromosome in Paramecium tetraurelia by Means of a Rolling Circle? - Preer, Louise B. (American Society for Microbiology, 1999)
The macronuclear genes coding for rRNA (ribosomal DNA [rDNA]) of Paramecium tetraurelia, stock 51, are arranged in polymers consisting of units made up of a transcribed coding region and a nontranscribed spacer region. The whole macronuclear polymer ends with a portion of the spacer on either end followed by a telomere. Six kinds of macronuclear units, or genes, were mapped. Spacers were different, and transcribed regions were the same. These genes are found in markedly different numbers in the macronucleus. The most common gene shows two regions in the spacer where a sequence is followed by a direct repeat. The next most common gene is similar but shows a deletion plus a number of base pair substitutions. Although most cosmid clones contain only a single kind of gene, many contain more than one. These are thought to be produced by somatic crossing over. The four micronuclear genes that have been isolated consist of a single central transcribed region and portions of the spacer on either end. Sequencing indicates that the two ends of the molecule are partially redundant. While the spacer region at the right end of the macronuclear polymer is derived from the micronuclear spacer on the right, the spacer at the left end of the macronuclear polymer is derived from regions of the micronuclear spacer on both the right and the left. To account for this situation, a rolling-circle model for generation of the macronuclear rDNA from the micronuclear DNA is proposed.